Serum Metabonomics Reveals Key Metabolites in Different Types of Childhood Short Stature - Guoyou Chen; Jinming Wang; Yisi Jing; Chunxiang Li; Wenyue Zhang; Shuang Yang; Ye Song; Xin Wang; Jincheng Liu; Dejun Yu; Zhichun Xu (Frontiers Media S.A., 2022)
Graphical AbstractSS, short stature; SDS, standard deviation scores; Control, normal height, n=30; ISS, idiopathic short stature n=31; GHD, short stature caused by growth hormone deficiency, n=29.